21st Century Slavery: Trafficking of women for sexual and commercial exploitation (UNIHumanitas, 2019)
The research presents the results of a review of documents published by international organizations, non-governmental organizations and academic works, used as a reference from 2012 to 2018, on human trafficking, sexual and commercial exploitation of women. The review was carried out in four phases and thematic analysis: a) legal and conceptual frameworks of the crime and its typologies, forms of operation of trafficking in women; b) approach to trafficking in Latin America, Spain and the United States; c) proposals to raise awareness about trafficking and d) relationship between trafficking and the media. Virtual databases of social sciences and two organizations that work on the subject of trafficking and sexual exploitation of women were used. The records were made in content sheets with the bibliographic data, the objective of the document, the methodology used, the sources cited, the results and the conclusions. The information was organized and classified according to the typology of trafficking in research, based on key definitions on the subject, characteristics, legal, political and economic aspects. The results indicate that between 2001 and 2015, the majority of research carried out in Latin American countries, Spain and the USA focused on trafficking associated with the sexual exploitation of women. There is less development of work on trafficking associated with filial relationships (servile marriage and adoption for the purpose of exploitation), commission of illicit acts (participation in different crimes such as drug transport and robbery) and organ trafficking.
Keywords: trafficking in persons; sexual exploitation; commercial exploitation of women